ANALISIS KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KOTA SORONG - Koibur, Martha Marice; Pangemanan, Sifrid; Sabijono, Harijanto (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Granting regional autonomy is intended to improve the effectiveness and efficiency of government administration in order to manage and take care of its own country, especially in development finance. Local Revenue (PAD) are all local revenues derived from economic resources native to the area, and one of the sources of revenue that have the largest contribution coming from the Regional Tax and Retribution. Local Taxes and Levies is one form of public participation in the implementation of otonomi area . local Taxes and levies a local revenue sources that are essential to finance the implementation of government and regional development. the aim of this study was to determine Contributions of local Taxes to PAD in Sorong. this research uses primer method. data analysis techniques used through the analysis of the percentage contribution. Based on the survey results revealed that in 2011 to 2014 local taxes was a contributing factor to the PAD. in the reception area is the largest tax contribution occurred in 2012 by 49%, while the lowest tax revenue occurred in 2010, namely 18%. And the contribution of each type of local tax receipts largest occurred in 2012 which amounted to 20,07% BPHTB tax and revenue realization is kind of the lowest tax registration tax perus.perdangan is 0,25% Keywords: Local Taxes and Local Revenue